An international point source outbreak of typhoid fever: a European collaborative investigation - Stanwell-Smith, R. E. (1986)
A point source outbreak of Salmonella typhi, degraded Vi-strain 22, affecting 32 British visitors to Kos, Greece, in 1983 was attributed by a case—control study to the consumption of a salad at one hotel. This represents the first major outbreak of typhoid fever in which a salad has been identified as the vehicle. The source of the infection was probably a carrier in the hotel staff. The investigation demonstrates the importance of national surveillance, international cooperation, and epidemiological methods in the investigation and control of major outbreaks of infection.